The Influence of the Addition of Graphene Loading on the Conductivity and Stability of Biopolymer Composite Solid Electrolyte - Salleh, Fauzani Md.; Hamid, Farzana Abd.; Mohamed, Nor Sabirin (Scientific Research, New Technologies and Applications Vol. 10, 2024)
Aims: To study the influence of the addition of graphene loading on the conductivity and stability of biopolymer composite solid electrolytes. Study Design: Solution-casting technique using sol gel method. Place and Duration of Study: Chemistry Research Laboratory, Level 2, PASUM Complex, Centre for Foundation Studies in Science, Kuala Lumpur between June 2016 until December 2018. Methodology: These composites were synthesized by mixing of alpha cellulose with graphene flakes via the solution-casting technique using sol gel method. The addition of graphene into composite was varied between 10 wt.% to 70 wt.%. Results: The X-ray diffraction (XRD) patterns revealed, at 60 wt. % graphene loading, XRD patterns exhibited the decrease in intensity at peak 260 indicating that graphene is more dispersed in the alpha cellulose mixture and reduced the crystallinity properties of biopolymer composite solid electrolyte. Electrochemical impedance spectroscopy was used to determine the conductivity of the composite. Sample without the addition of graphene acts as an insulator with the lowest conductivity value of 1.77×10-7 S cm-1. The highest conductivity achieved was 2.85×10-4 S cm-1 and observed at 60 wt.% graphene content. Fourier Transform InfraRed spectroscopy showed the absorption peaks of C-O stretching vibrations of composite was weakened and the hydroxyl group is slightly shifted compared to the one without the addition of graphene. This might relate to dehydration of cellulose. Thermogravimetric Analysis was used to study the thermal stability and decomposition of composite. The derivative thermogravimetric curves, showed two degradation peaks of composite. The first degradation peak (Tp1) occurred between ~70 to 1100C while the second degradation peak (Tp2) was between 250-4000C. Tp2 peak of composite with 60 wt.% and 70 wt.% were at 3000C and 2750C, respectively. This suggested that 60 wt.% graphene content has higher thermal stability compared to 70 wt.%. Linear sweep voltammetry results showed that the electrochemical stability of composite solid electrolytes exhibited up to 3.2 V. Conclusion: Biopolymer composite solid electrolyte with high conductivity was successfully prepared using an eco-friendly method. BmimCl ionic liquids are favorable in dissolving \(α\)-cellulose and aided graphene dispersion. An increase in graphene content has increased the conductivity of biopolymer composite provided that graphene is uniformly dispersed in a cellulose matrix. This research provided an eco-friendly method to prepare cellulose/graphene biopolymer composite which is useful in the energy field for future applications.